Determination of error-corrected full scattering parameters of a two-port device from uncalibrated measurements. (28th February 2022) - Hasar, Ugur Cem; Ozturk, Hamdullah; Korkmaz, Huseyin; Izginli, Mucahit; Alfaqawi, Mona Sadat Sophi; Ramahi, Omar Mustafa
Abstract: A methodology relying on relating terms of a two-port error network to the scattering (S-) parameters of a two-port network or device is applied to extract its full S-parameters. The new methodology has only one sign ambiguity problem (two solutions) in evaluation of S 11 (and thus S 22 ) while the similar methodology in the literature has two sign ambiguity problems (4 solutions). This ambiguity problem of our method is shown to be eliminated by applying an approach based on continuity of the argument of S 11 in the frequency domain. On the other hand, our methodology, as compared with the thru-reflect-line calibration technique, does not necessitate usage of any reflection standard in determining full S-parameters of a two-port network or device. Finally, it gives information about error networks. For its validation, S-parameters of a microwave phase shifter and a polyethylene sample flushed with the left/bottom terminal of the coaxial cell were extracted. Highlights: Error networks are related to scattering parameters of a two-port device. The new methodology has only one sign ambiguity problem in evaluation of S 11 . A continuity-based approach in frequency-domain is applied to eliminate this problem It does not necessitate usage of any reflection standard in determining full S-parameters. The proposed methodology gives information about error networks.